Termin „misy” w De medicina A.K. Celsusa: jego znaczenie i ekwiwalenty językowe w słownikach i przekładach traktatu - Kulikova, Natalia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The article presents a linguistic analysis of the term misy used in the recipes of A.C. Celsus’ treatise De medicina. An attempt to establish the designations of this lexeme, based on texts of ancient and modern authors, definitions in dictionaries and thesauruses, and scientific data from chemistry and mineralogy (modern), was made.